Leadership And Public Management: The Life Cycle Of The Management Position - Finn Jude (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
A growing body of research identifies the impact of leader characteristics on the strategy and results of organizations. This article, after carrying out a review of the literature on leadership, and in particular on the contributions of the literature on leadership in public management, concludes that the effects of leadership have been studied from a static perspective, in most cases. In order to overcome this limitation and include a dynamic and longitudinal analysis, it proposes to apply the concept of life cycle to the mandate of public managers, a topic that until now has not been addressed in the literature on public management. In the first place, it deals with the analysis of the horizontal career of the public manager throughout his term, as opposed to a traditional, vertical approach, of analysis of career promotion. That is, the life cycle during the management mandate. Secondly, the document identifies the key dimensions and stages in the public manager's life cycle during his mandate and makes the following proposals for the construction of an analysis model: 1) The public manager, at the beginning of his mandate , focuses its attention on achieving the objectives defined by its result indicators, with initial support from the political environment that appointed it. 2) In a second stage, he begins a period of exploration after having shown some achievements and not having endangered political trust. 3) It is in the third stage when the public manager can select the narrative by which his mandate in the organization will be recognized. To do this, he weaves internal information networks to develop a legitimate and feasible, long-term vision for the organization. 4) In the convergence stage is when the maximum results of the public manager are produced, since an inverted U-shaped relationship is manifested between the duration of the mandate and the results. 5) In the stage of dysfunction with the organization or managerial sclerosis, the power of the manager is maximum, as is the knowledge of the task. However, if the mandate is not limited in duration, the consequences for the organization can be lethargy or crisis. Finally, the article builds a research proposal that combines questionnaires based on scales recognized by the literature and semi-structured interviews for the exploratory analysis of the conceptual model and its propositions.